2016
DOI: 10.4236/oalib.1102728
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Lensing of Spiral Vortex Solar Radiation by Venus

Abstract: Instrumental observations of the Venus transit on June 6, 2012 were performed using two similar torsinds-a special kind of ultralight torsion balances on a silk suspension. A clear response of both devices to this phenomenon was registered. The observations have verified a theoretical assumption on existence of the Spiral Vortex Solar Radiation (SVSR). The direct measurements of a space velocity of the SVSR determined on the track Venus-Earth, gave a value of 1990 km/s which coincided almost exactly with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The Venus transit observations made it possible to determine accurately the speed of SVRS equal to 1990 km/s. These results are presented in details in [16].…”
Section: The Venus -Moon Conjunction On 16052010mentioning
confidence: 84%
See 2 more Smart Citations
“…The Venus transit observations made it possible to determine accurately the speed of SVRS equal to 1990 km/s. These results are presented in details in [16].…”
Section: The Venus -Moon Conjunction On 16052010mentioning
confidence: 84%
“…As the most important result remains the fact that both torsinds "caught sight" of the phenomenon only a few hours after its starting. It happened only at 5h 48m after the first contact when both devices began to increase their readings at the same time [16] The delayed reaction of both devices gives grounds to assume that the Venus transit caused some changes in the intensity of the solar radiation component that carries the torque effect. In theory, the existence of this component, called Spiral Vortex Radiation of the Sun (SVRS), was predicted by professor G.A.…”
Section: The Venus -Moon Conjunction On 16052010mentioning
confidence: 98%
See 1 more Smart Citation
“…Inertons can also travel like cluster-like formations of several or many excitations that have merged together, and in that case šœ can be reduced; such condensation of inertons can be related to the Bose-Einstein condensation phenomenon presented in real space. Recent experimental studies of other researchers [6], [7] have shown that some unknown previously massive particles were coming from the Sun to Earth and from Venus to Earth; the speed of those particles was estimated to be around 2,000 km/s. In the author's terms those massive particles have to be identified as clusters, or wavelets of inertons.…”
Section: B Free Inertonsmentioning
confidence: 99%
“…Their presence has also been measured in experiments conducted by many other researchers who emphasized the action of an unusual field but didn't identify them as inertons at the time. Various terms have been used to describe this or a similar field and the appropriate particles, most notably: tachyons [8], microleptons [9], torsion fields [10], axions [11], spirinos [7] and so on (e.g., see a very recent article about a null electromagnetic wave [12]).…”
Section: B Free Inertonsmentioning
confidence: 99%